Polycystic ovary syndrome and excessive body weight impact independently and synergically on fertility treatment outcomes - Emídio Vale-Fernandes; Mafalda V. Moreira; Raquel L. Bernardino; Daniela Sousa; Raquel Brandão; Carla Leal; Márcia Barreiro; Mariana P. Monteiro (Reproductive Biology and Endocrinology)
Abstract Background Polycystic ovary syndrome (PCOS) and obesity can both disrupt reproductive function. However, the extent to which obesity contributes to PCOS manifestations is not very clear. This study aimed to disentangle the relative contributions of PCOS and obesity for reproductive dysfunction in women undergoing in vitro fertilization (IVF). Methods A total of 129 women undergoing IVF treatments were recruited. Women were allocated into four groups according to body mass index (BMI) and PCOS diagnosis: normal-weight controls (n = 33; 21.70 ± 1.85 kg/m²), overweight/obesity controls (n = 28; 28.35 ± 3.05 kg/m²), normal-weight PCOS (n = 31; 21.92 ± 1.95 kg/m²), and overweight/obesity PCOS (n = 37; 31.67 ± 5.03 kg/m²). Circulating levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), anti-Müllerian hormone (AMH), glucose and insulin were measured in all groups, while insulin resistance was assessed by the Homeostatic Model (HOMA-IR). Additionally, on the oocyte retrieval day, ∆4-androstenedione, testosterone, progesterone and sex hormone-binding globulin (SHBG), were measured in plasma and follicular fluid (FF). IVF outcomes evaluated included the number of oocytes retrieved, oocyte immaturity, as well as fertilization and blastocyst formation rates. A multivariate analysis was performed to determine the independent effects of PCOS and obesity for reproductive and metabolic parameters. Results Women with PCOS presented significantly higher AMH levels, LH: FSH ratio, and lower FF progesterone levels, confirming these as PCOS-specific signatures regardless of BMI. In contrast, women with overweight/obesity had lower plasma and FF SHBG levels and greater HOMA-IR, independently of PCOS. Furthermore, ∆4-androstenedione and testosterone levels in plasma and FF were significantly higher in women with PCOS and overweight/obesity as compared to normal-weight women with PCOS. Despite the higher oocyte retrieval rates in women with PCOS, no differences in oocyte immaturity, fertilization and blastocyst formation rates were observed. Conclusions PCOS and obesity independently disrupt female reproductive function suggesting that features associated with each condition may differ. Furthermore, our study shows that obesity exacerbates hyperandrogenism in women with PCOS, highlighting a synergistic detrimental impact on female reproductive function.